Soft law i hard law w europejskim prawie administracyjnym: relacja alternatywy, uzupełnienia, wykluczenia oraz przejścia - Pietrzyk, Marcin (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The main aim of this article was to describe relations between ‘soft law’ and ‘hard law’ in the light of the European Administrative law. The author of the article defined four relations in the scope of above mentioned relations between ‘soft law’ and ‘hard law’, i.e. the relation of ‘alternative’, the relation of ‘complementarity’, the relation of ‘exclusion’ and relation of ‘transition’. Author also defined indispensable prerequisites, determining the existence of above mentioned relations. The article also points out the dynamic character of the ‘soft law’ which results in ability to encompass more relations which occur between ‘soft law’ and ‘hard law’.
Keywords: soft law; hard law; proportionality; subsidiarity; institutional balance